Characterizing Early Maternal Style in a Population of Guide Dogs - Bray, Emily E.; Sammel, Mary D.; Cheney, Dorothy L.; Serpell, James A.; Seyfarth, Robert M. (Frontiers in Psychology, 2017)
In both humans and non-humans, differences in maternal style during the first few weeks of life can be reliably characterized, and these differences affect offspring’s temperament and cognition in later life. Drawing on the breeding population of dogs at The Seeing Eye, a guide dog school in Morristown, New Jersey, we conducted videotaped focal follows on 21 mothers and their litters (n = 138 puppies) over the first three weeks of the puppies’ lives in an effort to characterize maternal style. We found that a mother’s attitude and actions toward her offspring varied naturally between individuals, and that these variations could be summarized by a single principal component, which we described as Maternal behavior. This component was stable across weeks, associated with breed, litter size, and parity, but not redundant with these attributes. Furthermore, this component was significantly associated with an independent experimental measure of maternal behavior, and with maternal stress as measured by salivary cortisol. In summary, Maternal behavior captured a significant proportion of the variation in maternal style; was stable over time; and had both discriminant and predictive validity.